Fine scale phenotypic diversity of Arctic charr in relation to ecological characters - Kristjánsson, Bjarni Kristófer (University of Guelph, 2008)
As biological diversity of the world is increasingly threatened, it is of great importance to map it and study factors that are important for its origin and maintenance. In recent years scientists have increasingly realized that there is a strong relationship between ecological dynamics and micro-evolutionary processes. To increase our understanding on important ecological factors related to the evolution of biological diversity, a comparative approach involving a high number of populations is powerful. Here, I have used this approach in studies on Icelandic Arctic charr ('Salvelinus alpinus') to gain further understanding of the relationship between ecological factors and phenotypic diversity. My results showed that ecological variables were related to phenotypic diversity of fish. For Arctic charr populations in lakes factors like age of bedrock, origin of water and fish community structure were clearly related to morphological diversity. Numerous populations of small benthic charr have evolved in lava springs in Iceland. These charr are morphologically similar, but differ, nevertheless, in important morphological features related to feeding. I found a clear relationship between diversity in morphology and diet and ecological factors among populations. In particular, there were clear differences in morphology and diet between fish coming from habitats where the lava spring flowed on as a stream compared to habitats where the lava spring flowed into a pond. Laboratory rearing experiments showed that phenotypic plasticity is important for morphological diversity. Populations differed in reaction norms for morphology and the level of plasticity was related to current velocity and amount of lava rock in their habitats. This strongly suggests that plastic responses have evolved within populations. Findings of this study strengthen ideas that ecological factors are important for the origin and maintenance of biological diversity. The relationship between phenotype and ecological factors is not only observed when ...